Mapping spatial patterns of groundwater discharge in a deep lake using high-resolution temperature sensors. Issue 3 (3rd July 2019) - Keim, Catharina; Mehler, Franziska; Wolf, Thomas; Gilfedder, Benjamin
ABSTRACT: Identifying groundwater discharge zones to lakes is important because the groundwater system can contribute a significant flux of water and solutes and potentially influence lake chemistry and ecology. We present a new instrument, Temperature Mapper (TM), to map groundwater discharge zones in lakes via temperature anomalies along the lake bottom, tested in Lake Constance at 2 former sand and gravel extraction sites. TM is essentially a 4 m wide sled with an array of 19 high-resolution sensors attached to an aluminum lattice towed along the lake bed behind a boat. It is able to map spatial temperature patterns representing groundwater discharge zones at a resolution of 20 cm laterally and 2.5 m in path direction. We conducted 2 field campaigns in February 2016 and February 2017, during which TM identified several temperature anomalies interpreted as groundwater discharging zones. Radon-222 was also analyzed at selected locations as an independent indicator of groundwater discharge. Overall, when comparing the different methods and different years, we observed similar spatial patterns of preferential groundwater discharge. TM offers a useful qualitative tool to identify and map potential groundwater discharge zones in lakes or coastal areas that can then be further studied by more quantitative, small-scale methods such as chemical tracers or seepage meters.